Multiple Looser zones of osteomalacia in Byler disease with associated vitamin D deficiency, phosphaturia, and elevated FGF23. (2016) - Tarazi, M.; Ellanti, P.; McKenna, M.J.; Kilbane, M.; McCormick, P.A.; Hurson, C.
Highlights: Byler disease is rare and stress fractures in this population are infrequently reported in literature. It is important to be aware of this complication of the disease because stress fractures can be a source of significant morbidity. Surveillance for osteomalacia and osteoporosis and treatment is advocated to prevent Looser zones and stress fractures in patients with Byler disease. Abstract: Introduction: Byler disease (progressive familial intrahepatic cholestasis) is associated metabolic bone disease as a consequence of chronic malabsorption. Case presentation: A 33-year-old man with decompensated liver disease secondary to Byler disease was referred to the orthopaedic department with progressive pain over this right proximal tibia. On examination, he had an antalgic gait. Tenderness was localised to the proximal tibia just distal to the tibial tubercle and bilateral foot swelling. Radiographs showed multiple stress fractures characteristic of Looser zones at various stages of healing in both tibia, metatarsals (third, fourth, and fifth on the right side, and second and fourth on the left) and left femur. Bone mineral density was extremely low. Subsequent investigations were consistent with severe osteomalacia due to a combination of vitamin D deficiency and phosphaturia with elevated fibroblast factor 23 (FGF23). A good clinical response was achieved following supplementation with calcium 1000 mg and vitamin D 20 μg daily. Discussion: Stress fractures are often associated with delay in diagnosis. Our patient presented to the orthopaedic service with multiple Looser zones that had not been previously detected. As expected, there was biochemical evidence of vitamin D deficiency. An unexpected finding was phosphaturia that was associated with marked elevation in FGF23, which has never been reported previously. Conclusion: Byler disease may result in Looser zones of osteomalacia due to chronic malabsorption. Renal phosphorus wasting as a consequence of unexplained marked elevation in FGF23 is thought to have contributed to the onset of osteomalacia.